Synchronous gubernacular canals with compound odontoma associated with a calcifying odontogenic cyst and transmigrated canine: An extremely rare event. Issue 1 (April 2020) - Brooks, John K.; Tran, Linh T.; Basile, John R.; Khoury, Zaid H.; Wu, Lawrence L.; Price, Jeffery B.
Abstract: This article reports the novel incidental concurrences of multiple oral lesions in a 13-year-old boy. Radiographically, an over-retained primary canine was seen with a subjacent mixed radiopacity and transmigrated permanent canine with a suspected dentigerous cyst (each with gubernacular canals). Treatment consisted of enucleation and removal of the impacted canine. The histopathologic findings were compound odontoma containing multiple tooth-like structures and calcifying odontogenic cyst with epithelium containing ghost cells, calcifications and subjacent fibrous connective tissue wall. All cases of odontomas should undergo microscopic assessment for diagnosis and ascertainment of associated pathosis.